The Effect of Job Stress, Work From Home Policy, and Effective Communication on Employee Performance (A Study on the Quality Assurance Division of PT. Kobus Smart Service) - Hidayatulloh, Taopik; Affini, Dinar Nur; Lestari, Nurul Sukma (Universitas Mercu Buana, 2025)
Abstract – This study aims to analyze the effect of job stress, Work From Home (WFH) policies, and effective communication on the performance of employees in the Quality Assurance division at PT. Kobus Smart Service. The research adopts a quantitative descriptive approach, targeting all 44 permanent employees through a saturated sampling method. Data were collected using surveys and structured questionnaires. The findings reveal that job stress has a significant negative impact on employee performance, indicating that heightened stress levels reduce focus and effectiveness. Conversely, the WFH policy and effective communication exhibit a significant positive influence on performance, suggesting that flexible working arrangements and clear communication enhance productivity and employee satisfaction. These results underscore the importance of stress management strategies, the integration of WFH practices, and fostering effective communication to optimize employee performance. The study contributes both theoretically and practically to human resource management by identifying key factors influencing employee performance in the outsourcing sector. Keywords: Job Stress, Work From Home Policy, Effective Communication, Employee Performance